Knowledge, attitude, and practice of dietary fibre consumption among International Islamic University Malaysia (IIUM) students - Kamarul Azman, Fatima Zahrah; Azahari, Nuraniza (IIUM Press, International Islamic University Malaysia, 2024)
Background: Dietary fibre provides many advantages to human health and can be found in fruits, vegetables, grains, and other plant-based foods. It has been proven that intake of dietary fibre is low globally and while interventions should focus on all age groups, those targeting young adults should be given priority. Therefore, this study intends to assess the knowledge, attitude, and practice (KAP) of dietary fibre consumption among International Islamic University Malaysia (IIUM) undergraduate students. Methods: A cross-sectional study was employed, and the sample population consisted of students of IIUM Kuantan, Gombak, and Pagoh. A validated KAP survey adopted from a previous study was used. The survey was created using Google Forms and disseminated through online platforms. A total of 381 students (190 health science and 191 non-health science) participated in this study. Results: The results found that the students had moderate levels of knowledge (69.7 ± 10.3%) and practice (57.3 ± 18.3%), as well as high positive attitude (86.5 ± 10.1%) towards dietary fibre consumption. There were no significant differences in KAP scores between health science and non-health science students. Nonetheless, there was a significant relationship between knowledge and practice (p = 0.022), and between attitude and practice (p < 0.001). On the other hand, no significant relationship was found between knowledge and attitude (p = 0.587). Conclusion: Nutritional interventions that incorporate aspects of knowledge and attitudes should be developed to promote better practices and habits of dietary fibre consumption among university students.